0052 A mixed-methods examination of perceived challenges during the COVID-19 pandemic: Associations with sleep health and nightmares among healthcare workers. (25th May 2022) - Franzen, Ronald; Kahlon, Ramandeep; Jones, Melissa; Agrawal, Ritwick; Crew, Earl
Abstract: Introduction: The emergence of CoVID-19 has created an immense burden on healthcare systems across the world, placing healthcare workers (HCWs) under significant, additional stress while they also confront multiple personal, family and sociopolitical challenges during the pandemic. Many studies have reported the negative impact of pandemic-related stress on sleep of HCWs. Our mixed-methods investigation sought to extend existing research by characterizing the themes of HCWs' primary concerns during the early pandemic and identifying the most salient concerns which might be impacting sleep. Methods: North American HCWs (n = 1331) were surveyed during the "second wave" of CoVID-19 case increases (6/9/2020 – 8/17/2020), which included a questionnaire with measures of sleep health (RU-SATED) and nightmare frequency (PSQI). Additionally, each HCW was asked to openly-describe their most salient concern with regard to the pandemic. Each response was categorized by topic. T-tests were conducted to compare frequencies of each response category with sleep health and nightmare frequency. Results: The study sample comprised 1331 HCWs (91.7% female; 74.5% non-Hispanic white; 64.31% with exposure to CoVID-19 patients; 85.1% working in-person). Primary concerns were grouped into 8 categories including combinations of personal/familial-level concerns (e.g. concern about CoVID-19 infection/spread), and work-related stressors (e.g. increased workload). Concerns about lack of PPE/equipment was significantly associated with lower scores on RU-SATED (t = -2.69; p = .007) and increased nightmare frequency (t = 2.70; p = .007). Additionally, concerns about increased workload were significantly associated with lower scores on both RU-SATED (t = -2.79; p = .005) and increased nightmare frequency (t = 5.24; p = .000). Individually, primary concerns for CoVID-19 infection/spread was significantly associated with more-frequent nightmares (t = 2.01; p = .045). Neither sleep measure was associated with categories involving societal-level concerns (e.g. sociopolitical concerns) among the sample. Conclusion: Our results indicate that the HCWs most concerned about workplace stressors during the pandemic indicated poorer sleep health and more frequent nightmares. Further analyses could help guide proper stratification of therapeutic approaches to improve sleep health and related distress for HCWs. Support (If Any):